Pengaruh Brand Image, Kemasan Produk dan Harga Terhadap Keputusan Pembelian Pada Produk Perawatan Wajah Emina - Nadia Putri Rahmatika; Budi Wahono; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study used a quantitative approach to ascertain the impact of Brand Image, Product Packaging, and Pricing on Buying Choices for Emina's beauty goods. 90 respondents were included in the study's sample, which was calculated using the Slovin formula. Primary data collected through a questionnaire is what was used. The validity and reliability of the instruments, as well as tests for normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, simultaneous tests, partial tests, and coefficient of determination, were all utilized in this work. According to the research's partial findings, Brand Image has a favorable and large impact on purchasing decisions, but Product Packaging has no impact and Pricing has a marginally significant impact. From the research that has been done, the results show that brand image is more influential than the other two variables.  Keywords: Brand Image, Product Packaging, Price and Purchase Decision